2011
DOI: 10.1186/1471-2164-12-556
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of orange-spotted grouper (Epinephelus coioides) spleen in response to Singapore grouper iridovirus

Abstract: BackgroundOrange-spotted grouper (Epinephelus coioides) is an economically important marine fish cultured in China and Southeast Asian countries. The emergence of infectious viral diseases, including iridovirus and betanodavirus, have severely affected food products based on this species, causing heavy economic losses. Limited available information on the genomics of E. coioides has hampered the understanding of the molecular mechanisms that underlie host-virus interactions. In this study, we used a 454 pyrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(80 citation statements)
references
References 59 publications
(55 reference statements)
7
67
0
2
Order By: Relevance
“…Previous studies in other fish species have reported changes in the spleen transcriptome profile following exposure to antigens and chemicals, as well as temperature stress, thereby providing insight into immune-relevant genes and pathways. Examples of these species are the zebrafish (Danio rerio) [5], orange-spotted grouper (Epinephelus coioides) [6], large yellow croaker (Pseudosciaena crocea) [7,8], Atlantic cod (Gadus morhua) [9e11], Asian seabass (Lates calcarifer) [12], and channel catfish (Ictalurus punctatus) [13]. However, current knowledge regarding fish spleen is still fragmentary, and very little is known about the molecular processes in the fish spleen during normal development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in other fish species have reported changes in the spleen transcriptome profile following exposure to antigens and chemicals, as well as temperature stress, thereby providing insight into immune-relevant genes and pathways. Examples of these species are the zebrafish (Danio rerio) [5], orange-spotted grouper (Epinephelus coioides) [6], large yellow croaker (Pseudosciaena crocea) [7,8], Atlantic cod (Gadus morhua) [9e11], Asian seabass (Lates calcarifer) [12], and channel catfish (Ictalurus punctatus) [13]. However, current knowledge regarding fish spleen is still fragmentary, and very little is known about the molecular processes in the fish spleen during normal development.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high-throughput transcriptome sequencing has facilitated the functional genomic study of fish and has provided insights into the immunogenetics of fish. For example, previous studies have discovered the immune-relevant genes following exposure to pathogenic microorganisms through de novo transcriptome sequencing in several aquaculture fish species, including orangespotted grouper (E. coioides) [6], large yellow croaker (P. crocea) [7,8], turbot (Scophthalmus maximus) [17], Japanese sea bass (Lateolabrax japonicus) [18] and rohu carp (Labeo rohita, Hamilton) [19]. However, to our knowledge, the de novo sequencing of the spleen transcriptome of fish has been limited to only a few species, and this has hindered the progress of immunological research.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale analyses of transcriptome response to viral infection have been carried out in a number of other fish species, including Atlantic salmon head kidney cell response to SAV-1 (12), Atlantic salmon heart response to piscine myocarditis virus (13), orange-spotted grouper spleen response to Singapore grouper iridovirus (14), response of the grouper kidney cell line infected by betanodavirus (15), and Atlantic cod brain response to nervous necrosis virus (16). These studies generally addressed the transcriptional response of a particular tissue after infection with a given virus, and resulted in overlapping but largely distinct sets of modulated genes.…”
mentioning
confidence: 99%
“…The primers used for RACE PCR (Table 1) were designed based on the identified expressed sequence tag (EST) sequence from the transcriptome library established in our laboratory (Accession No. SRA040065.1) [28], In detail, the gene specific primer c-Jun 5 0 NGSP1, c-Jun 3 0 GSP1 (Table 1) and UPM (supplied by the kit) were used for the first round PCR. The PCR was conducted at 94 C for 3 min, followed by 30 cycles of 94 C for 30 s, 68 C for 30 s and 72 C for 50 s. The product of the first round PCR was diluted 10 times and then used as the template for the nested PCR.…”
Section: Cloning and Sequencing Of E Coioides C-jun (Ec-c-jun)mentioning
confidence: 99%